Surgery and chemotherapy cannot improve the survival of patients with early-stage mucosa-associated lymphoid tissue derived primary pulmonary lymphoma - Lin, Huahang; Zhou, Ke; Peng, Zhiyu; Liang, Linchuan; Cao, Jie; Mei, Jiandong (Frontiers in Oncology, 2022)
Background: To date, there is no treatment consensus on mucosa-associated lymphoid tissue (MALT) derived primary pulmonary lymphoma (PPL). Methods: We identified patients with early-stage MALT-type PPL from the National Cancer Institute's Surveillance, Epidemiology, and End Results program database. The patients were divided into four groups according to treatment modalities: None of surgery or chemotherapy (None) group, Surgery alone group, Chemotherapy alone (Chemo alone) group, and Surgery plus chemotherapy (Surgery + chemo) group. Overall survival (OS) and cancer-specific survival (CSS) were study endpoints. We performed Cox regression analyses, propensity score-matched analyses (PSM) and Kaplan-Meier (KM) survival curves to compare the survival among different groups. Results: A total of 953 patients were included in our analysis with 302, 403, 175, and 73 cases in the None, Surgery alone, Chemo alone, and Surgery + chemo groups, respectively. In this cohort, the estimated 3-year, 5-year and 10-year OS rates were 86.95%, 78.91%, and 55.89%, respectively. Meanwhile, the estimated 3-year, 5-year and 10-year CSS rates were 96.71%, 93.73%, and 86.84%, respectively. Multivariate Cox regression analyses demonstrated that increasing age, tumors located in the lower lobe, and stage II were significant predictors of poorer OS while increasing age and tumors located in the bilateral lungs were associated with lower CSS. After PSM analyses, the KM survival curves showed no significant differences in OS or CSS among the four groups. Conclusion: Early-stage MALT-type PPL is indolent in nature. Neither surgery, chemotherapy nor a combination of surgery and chemotherapy can improve OS and CSS, suggesting that “watch and wait” may be a reasonable alternative.